Chidamide stacked in magnetic polypyrrole nano-composites counter thermotolerance and metastasis for visualized cancer photothermal therapy. (31st December 2022) - Wang, Sizhen; Ma, Zhiqiang; Shi, Zhang; Huang, Ying; Chen, Tianheng; Hou, Lei; Jiang, Tao; Yang, Feng
Abstract: Photothermal therapy (PTT) has become one of the most promising therapies in cancer treatment as its noninvasiveness, high selectivity, and favorable compliance in clinic. However, tumor thermotolerance and distal metastasis reduce its efficacy, becoming the bottleneck of applying PTT in clinic. In this study, a chidamide-loaded magnetic polypyrrole nanocomposite (CMPP) has been fabricated as a visualized cancer photothermal agent (PTA) to counter tumor thermotolerance and metastasis. The efficacy of CMPP was characterized by in vitro and in vivo assays. As a result, this kind of magnetic polypyrrole nanocomposites were black spherical nanoparticles, possessing a favorable photothermal effect and the suitable particle size of 176.97 ± 1.45 nm with a chidamide loading rate of 12.92 ± 0.45%. Besides, comparing with PTT, CMPP exhibited significantly higher cytotoxicity and cellular apoptosis rate in two tumor cell lines (B16-F10 and HepG2). In vivo study, the mice showed obvious near-infrared (NIR) and magnetic resonance imaging (MRI) dual-modal imaging at tumor sites and sentinel lymph nodes (SLNs); on the other hand, magnetic targeting guided CMPP achieved a cure level on melanoma-bearing mice through preventing metastasis and thermotolerance. Overall, with high loading efficiency of chidamide and strong magnetic targeting to tumor sites and SLNs, CMPP could significantly raise efficiency of PTT by targeting tumor thermotolerance and metastasis, and this strategy may be exploited therapeutically to upgrade PTT with MPP as one of appropriate carriers for histone deacetylase inhibitors (HDACis).